Risk for Irritable Bowel Syndrome in Fibromyalgia Patients: A National Database Study. Issue 14 (April 2017) - Yang, Tse-Yen; Chen, Chih-Sheng; Lin, Cheng-Li; Lin, Wei-Ming; Kuo, Chua-Nan; Kao, Chia-Hung
Abstract : Abstract: Various studies have shown that irritable bowel syndrome (IBS) is highly associated with other pathologies, including fibromyalgia (FM). The objective of this study was to analyze the differences among risk factors associated with IBS following FM in a nationwide prospective cohort study. We propose that a relationship exists between FM and IBS. This article presents evidence obtained from a cohort study in which we used data from the Taiwan National Health Insurance Research Database to clarify the relationship between FM and IBS. The follow-up period ran from the start of FM diagnosis to the date of the IBS event, censoring, or December 31, 2011. We analyzed the risk of IBS using Cox proportional hazard regression models, including sex, age, and comorbidities. During the follow-up period, from 2000 to 2011, the overall incidence of IBS was higher in FM patients than in non-FM patients (7.47 vs 4.42 per 1000 person-years), with a crude hazard ratio = 1.69 (95% confidence interval [CI] 1.59–1.79). After adjustment for age, sex, and comorbidities, FM was associated with a 1.54-fold increased risk for IBS. Mutually risk factors may influence the relationship between FM and IBS. We recommend that physiologists conduct annual examinations of FM patients to reduce the incidence of IBS progression.